DISEASES CAUSED BY THE USE OF PESTICIDES IN AGRICULTURE - pcadmin, G.K. Rakhmatullayeva; N.A. Axmedova; M.A.Ubaydullayeva (Scholar Express Journals, 2025)
This article analyzes the impact of pesticides widely used in agriculture on human health. It examines the ways pesticides enter the human body and their harmful effects on the respiratory, nervous, endocrine and other systems. Additionally, preventive measures to reduce the risks associated with pesticide exposure are highlighted.
Keywords: Pesticides; agriculture; human health